Restricted Detour Polynomials of Straight Chains of Graphs - Mohammed-Saleh, Gashaw A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Recurrence relations for the restricted detour polynomials of straight chains of vertex identified and edge-introducing graphs are obtained. Then, restricted detour polynomials for chains of hexagons and pentagons are also obtained with their restricted detour indices.
Keywords: Restricted detour distance; Restricted detour diameter; Restricted detour index; Restricted detour Polynomials; Chains of graphs